Transient exposure to coffee as a trigger of a first nonfatal myocardial infarction - Baylin, Ana (2006)
Background: The effects of coffee on myocardial infarction are uncertain. We hypothesize that coffee in the presence of predisposing factors can induce a cascade of events that, through sympathetic nervous activation, can induce the onset of myocardial infarction. Methods: We recruited 503 incident cases of nonfatal myocardial infarction between 1994 and 1998 in Costa Rica. We used a case-crossover design to calculate relative risks (RRs) and 95% confidence intervals (95% CIs). Results: The RR of myocardial infarction in the hour after coffee intake was 1.49 (95% CI = 1.17–1.89). Occasional coffee drinkers (≤1 cup/day, n = 103) had a RR of myocardial infarction of 4.14 (2.03–8.42), moderate coffee drinkers (2–3 cups/day, n = 280) had a RR of 1.60 (1.16–2.21), and heavy coffee drinkers (≥4 cups/d, n = 120) had a RR of 1.06 (0.69–1.63; P = 0.006, test of homogeneity). Patients with 3 or more risk factors (n = 101) had a RR of myocardial infarction of 2.10 (1.30–3.39), whereas patients with fewer than 3 risk factors (n = 396) had a RR of 1.39 (1.04–1.82; P = 0.15, test of homogeneity); and RR was 1.72 (1.30–2.30) among sedentary patients compared with 1.07 (0.66–1.72) among nonsedentary (P = 0.10, test of homogeneity). Conclusions: The findings indicate that coffee intake may trigger myocardial infarction. The association is particularly strong among people with light/occasional intake of coffee (≤1 cup/day), with sedentary lifestyle, or with 3 or more risk factors for coronary heart disease.